Production of abiotic or biogenic hydrocarbons on rock particles in the presence of H2O and carbon compounds - Cho, Young Sang; Oh, In-Hwan; Kim, Ju Hee; Kim, Jae Ik; Lee, Kang-Bong; Nah, In Wook (Nature Publishing Group, 2025)
Abiotic H2 and hydrocarbons are found in fluids discharged from ultramafic-hosted hydrothermal vents. Beneath the hydrothermal vents, abiotic H2 and hydrocarbons can be formed by serpentinization reactions and Fischer-Tropsch-type hydrocarbon-forming reactions, respectively, over ultramafic rocks. However, the source rocks that form abiotic H2 and hydrocarbons may extend to broader subsurface rocks. Here, we show that various rock constituents (solid acids) play a catalytic role in the formation of H and OH radicals via H2O dissociation, as well as in the formation of diverse hydrocarbons via the synthesis reactions of H radicals and inorganic carbons or by H radical-induced dissociation of organic carbons. The mechanisms and characteristics of these formation processes were explored through a series of reactor-based laboratory experiments. Four types of solid acid-containing rocks were mixed with H2O and a carbon source and reacted at different temperatures and pressures for different reaction periods. The product gases were analyzed via GC/MS. Twenty-nine hydrocarbons up to C11, predominantly including CH4 and aromatic hydrocarbons, were identified when CO2 (inorganic carbon source) and basalt particles were used; in contrast, 42 hydrocarbons up to C11, predominantly including CH4 and aliphatic hydrocarbons, were identified when soybean oil (organic carbon source) and basalt particles were used. The results of this study imply that abiotic H2 and diverse hydrocarbons are produced in the subsurface of Earth regardless of the presence of living organisms and suggest that solid acid-containing rocks near hot springs or volcanic areas can promote CO2 conversion into CH4 with the aid of H radicals supplied from H2O dissociation over the rocks.